PENGEMBANGAN MODEL PEMBELAJARAN BERORIENTASI KKNI YANG MELIBATKAN KECERDASAN EMOSIONAL - Binur Panjaitan; Hulman Sihombing; Oktober Tua Aritonang; Betty A.S. Pakpahan; Rafita Tioria Sianipar (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2020)
The root of the problem in this study is the fact that student learning achievement is less satisfying, and learning that has occurred so far does not involve emotional intelligence. The problem in this study is